Effect of amount of coconut residue flour, its fat content and the use of antioxidant on consumer acceptability of a hotcake mix - Mabanta, Mary Christine P.
The effects of the amount of coconut residue flour (CRF) (0, 15, and 30% substitution of the All-purpose flour), antioxidant used and fa content of CRF (23, 28 and 33%) on the sensory properties of a hot cake mix were investigated. Twenty-four consumer panelists evaluated acceptability of cooked hotcake mix samples using 9-point hedonic scales. Verification tests were conducted using two treatments, one each from within and outside the optimum formulation. Results indicated that hotcake mixes wi9th 15% CRF substituted for the All-purpose flour were most acceptable to consumers when BT was used as the antioxidant. Any level of fat in the CRF produced acceptable products. However, a formulation that utilized CRF with 23% fat received highest consumer acceptance scores. Verification tests confirmed all these results.